Pemanfaatan ekstrak Wortel (Daucus carrota L.) sebagai imunostimulan pada ikan Kakap Putih (Lates calcarifer) - Aris, Muhammad; Juharni, .; Abdullah, Taufiq (Universitas Sam Ratulangi, 2019)
This study aims to determine the effect of carrot extract on the phagocyte activity of Vibrio alginolyticus in white snapper. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used respectively as follows, treatment A: 0 µl extract/individu, B: 100 µl extract/individu, C: 150 μl extract/individu, and D: 200 μl extract/individu. The average value of phagocytic activity tended to increase, namely treatment A 8.67%; treatment B 9.33%; treatment C 11.00%; and treatment D 14.00%. Carrot extract can increase phagocytic activity of white snapper. An effective dose that can increase the immune response of white snapper was 200 µl extract/individu of fish.